THE EFFECTIVENESS OF KNOW-WANT TO KNOW-LEARNED (KWL) STRATEGY IN READING COMPREHENSION - Dian Rakhmawati, author (JURNAL SMART, 2015)
The objectives of this research are to identify the effectiveness of KWL as the strategy in teaching reading comprehension to the second grade students of SMA Muhammadiyah 2 Metro. The quantitative research was conducted and this study is population research, because all the member of population is taken as sample, which consisted of 41 students of XI IPA class.To collects the data the researcher used pre-test and post-test. The test is in the form of multiple choices. To know whether there is a significantly difference between the studentsâ pre-test scores with their post-test scores, the writer analyzed the data by using Paired Sample T-test. Before the instrument was used in a research, the instruments of pre-test and post-test has been tried out in order to achieve good validity and reliability. The research findings show that in the pre-test, the studentsâ lowest score was 62.50 and the highest score was 80.00 with the mean 70.0000. Meanwhile, in the post-test, the studentsâ lowest score was 62.50 and the highest score was 90.00 with the mean 72. 4390. It means that KWL strategy is effective in teaching reading comprehension. It can also be proved by value of t-test with probability (Asymp.Sig.2 tailed) was less than the level of significance (0.002 < 0.05).Keywords : Effectiveness; KWL Strategy; Reading Comprehension.